Gold and indium electroplating process and preparation method thereof

Through the introduction of 铟 and anti -abrasion agent in citrate gold -plated solution, optimizing the electroplating process parameters, the problem of low hardness of the traditional electroplating technology in the traditional electroplating process has significantly improved the hardness and abrasion resistance of the plating, enhanced the gold -plated workpiece Durability.

CN119372728APending Publication Date: 2025-01-28NANJING COLLEGE OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411589490.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the traditional electroplating process, the obtained gold plating layer has a low microhardness and is prone to wear, affecting the durability of the gold-plated workpiece.

Method used

By introducing citron plating solution in citric acid, and optimizing process parameters, such as pH value, temperature, and current density, a gold -plated layer doped with 铟 is formed. The hardness of the coating.

Benefits of technology

It significantly improves the hardness and abrasion resistance of the gold -plated layer, enhanced the durability of gold -plated workpieces, and overcomes the problem of low hardness in the traditional process.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of electroplating, and particularly discloses a gold and indium electroplating process. According to the method, indium is introduced into the citrate gold plating solution in the form of indium citrate, the temperature, the pH value, the current density, the gold concentration and the indium concentration are optimized, and the indium-doped gold plating layer can be formed on the surface of the workpiece. The doping of indium can improve the hardness of the gold plating layer, is beneficial to reducing the wear of the gold plating layer, and improves the durability of the gold-plated workpiece.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electroplating technology, and more specifically, to a gold-indium electroplating process and a preparation method thereof. Background Art

[0002] Gold has good electrical conductivity, and has excellent properties such as wear resistance, high temperature resistance, and easy welding, making it suitable as a functional coating on the surface of workpieces. Among the traditional gold plating processes, electroplating gold occupies a large proportion. The principle of electroplating gold is to use the workpiece as the matrix material, and reduce the gold ions (usually in the form of complex ions) in the electroplating solution under the action of the electric field through the telephone line reaction on the surface of the workpiece, and deposit the generated gold element on the surface of the workpiece, so as to achieve electroplating of the workpiece.

[0003] In the related art, there is a gold electroplating process, which uses the following process parameters: gold concentration 4g / L, citrate concentration 105g / L, citric acid concentration 35g / L, pH value 5, temperature 40°C, current density 0.2A / dm 2 The anode material is a platinum-plated titanium mesh, and copper is the electroplating base material. The copper is pre-nickel-plated before gold plating. The citrate includes potassium citrate, sodium citrate, and ammonium citrate.

[0004] With respect to the above-mentioned related technologies, the inventors believe that although the electroplating of copper workpieces with gold can be achieved according to the process conditions in the related technologies, the gold plating layer obtained in this way has a low microhardness and is therefore prone to wear, which has a certain impact on the durability of the gold-plated workpiece. Summary of the invention

[0005] In the related art, the gold coating obtained by electroplating has a low microhardness and is therefore prone to wear, which has a certain impact on the durability of the gold-plated workpiece. In order to improve this defect, the present application provides a gold-indium electroplating process.

[0006] The present application provides a gold-indium electroplating process, which adopts the following technical solution: A gold-indium electroplating process comprises the following steps: (1) sequentially subjecting the workpiece to organic solvent degreasing, chemical degreasing, pickling and rust removal, pickling and activation, pre-nickel plating, and citric acid immersion treatment, and setting aside; the pre-nickel plating treatment forms a 2.3-2.8 mm thick nickel plating layer on the surface of the workpiece; (2) In a citrate plating solution with a pH of 4-5 and a temperature of 40-60°C, the 2The workpiece is subjected to gold plating treatment at a current density of , and the workpiece is recovered after the treatment, and the gold-plated workpiece is obtained after alcohol washing and drying; the components of the citrate gold plating solution include a main salt and a citrate, the main salt includes potassium gold cyanide, the citrate includes indium citrate, and the gold concentration and indium concentration of the citrate gold plating solution are 4-10g / L and 1-10g / L respectively.

[0007] By adopting the above technical solution, the present invention introduces indium into the citrate gold plating solution in the form of indium citrate, and optimizes the indium concentration and gold concentration of the citrate gold plating solution, and also limits the pH range and temperature range of the citrate gold plating solution. Within this range, the indium concentration is 0.2-1.5A / dm 2 After the workpiece is gold-plated at a current density of , a gold plating layer hard-doped with indium can be formed on the surface of the workpiece. The doping of indium can significantly increase the hardness of the gold plating layer, making the gold plating layer exhibit stronger wear resistance, thereby enhancing the durability of the gold-plated workpiece and overcoming the defects in the relevant technology.

[0008] Preferably, the main salt also includes potassium citrate gold, and the concentration of the potassium citrate gold is 2-3 g / L.

[0009] By adopting the above technical solution, the present application preferably uses potassium citrate gold as the second component of the main salt, and preferably uses potassium citrate gold in a dosage range. The addition of potassium citrate gold can not only reduce the use of potassium gold cyanide, but also the resulting gold plating can still have good hardness performance.

[0010] Preferably, in step (2) of the process, the current density is selected to be 0.3-0.9 A / dm 2 , the components of the citrate electroplating solution also include potassium antimony tartrate.

[0011] By adopting the above technical solution, the present application introduces potassium antimony tartrate to adjust the citrate gold plating solution, thus overcoming the limitation of potassium citrate gold plating solution at 0.3-0.9A / dm 2 The defect of poor deposition effect under current density conditions helps to obtain a gold plating layer with higher hardness.

[0012] Preferably, the concentration of potassium antimony tartrate is 0.08-0.26 g / L.

[0013] By adopting the above technical solution, the present application optimizes the dosage range of potassium antimony tartrate, which helps to fully realize the improvement effect on the hardness of the gold plating layer.

[0014] Preferably, in step (2), before the workpiece is subjected to gold plating, an anti-wear agent is added to the citrate gold plating solution, wherein the anti-wear agent comprises nano-silicon carbide, and the addition amount of the nano-silicon carbide is 2-8 g / L.

[0015] By adopting the above technical scheme, the present application preferably uses nano silicon carbide as an anti-wear agent. During the electroplating process, nano silicon carbide can migrate under the action of electric field force and co-deposit on the workpiece surface with gold particles, and finally obtain a gold coating containing nano silicon carbide. Anti-wear agents represented by nano silicon carbide can increase the number of grain boundaries inside the coating, and aggravate the dislocation accumulation inside the gold coating, hinder the movement of dislocations and the expansion of microcracks, and also limit the slippage of the grains themselves, which strengthens the gold coating, thereby further improving the hardness of the gold coating and improving the anti-wear performance of the gold coating.

[0016] Preferably, the anti-wear agent is added to the citrate gold plating solution according to the following method: The anti-wear agent is mixed with a portion of the citrate gold plating solution, and then the mixture is added into a plating tank containing the citrate gold plating solution and magnetically stirred. During the stirring process, a dispersant is added into the plating tank. After stirring for a period of time, ultrasonic dispersion treatment is performed to complete the addition of the anti-wear agent.

[0017] By adopting the above technical scheme, the present application first adds the anti-wear agent to a part of the citrate gold plating solution, then transfers it to the plating tank to mix with more citrate gold plating solution, then successively performs magnetic stirring and ultrasonic dispersion, and adds a dispersant. Through the above processing flow, the anti-wear agent is fully dispersed, the agglomeration of the anti-wear agent is reduced, and it is beneficial to the full deposition of the anti-wear agent particles on the workpiece surface.

[0018] Preferably, the added amount of the nano-silicon carbide is 5-8 g / L.

[0019] By adopting the above technical solution, the present application optimizes the addition amount of nano-silicon carbide, which helps to fully improve the hardness performance of the gold plating layer.

[0020] Preferably, the anti-wear agent further comprises modified silicon carbide, and the modified silicon carbide is prepared according to the following method: (1) using distilled water to wash the wear-resistant silicon carbide, then drying the nano silicon carbide, mixing the nano silicon carbide and toluene, stirring for a period of time under nitrogen protection, then adding a silane coupling agent and continuing to stir and react for a period of time, filtering while hot after the reaction is completed, soaking in acetone and then filtering to obtain silanized silicon carbide; the silane coupling agent is KH550 and vinyl triethoxysilane; (2) Silylated silicon carbide and acrylamide are added to deionized water, an initiator is added under nitrogen protection, the mixture is stirred for a period of time, and then filtered, washed and dried to obtain modified silicon carbide; the amount of acrylamide used is 1.5-3.5% of the weight of the silanized silicon carbide.

[0021] By adopting the above technical scheme, the present application introduces amino and vinyl groups on the surface of nano silicon carbide through the treatment of silane coupling agent, obtains silanized silicon carbide, and then grafts the polymer chain segments formed by acrylamide to the surface of silanized silicon carbide under the action of initiator, thereby obtaining modified silicon carbide. The surface of modified silicon carbide has a large number of amino groups, which are protonated in the acidic environment of citrate gold plating solution and carry positive charge, and can migrate to the surface of the workpiece more easily under the action of electric field, which helps to fully improve the hardness performance of the gold plating layer.

[0022] Preferably, the amount of acrylamide used is 2.9-3.5% by weight of the silanized silicon carbide.

[0023] By adopting the above technical solution, the present application optimizes the amount of acrylamide, which helps to increase the total amount of amino groups on the surface of modified silicon carbide, promotes the deposition of modified silicon carbide on the surface of the workpiece, and helps to improve the hardness performance of the gold plating.

[0024] Preferably, the added amount of the modified silicon carbide is 2.7-4.2 g / L.

[0025] By adopting the above technical solution, the present application optimizes the addition amount of modified silicon carbide. Under this addition amount condition, the total amount of anti-wear agent can be maintained at a relatively low level, and the gold plating layer can maintain good hardness performance.

[0026] In summary, this application has the following beneficial effects: 1. The present application introduces indium into the citrate gold plating solution in the form of indium citrate, and optimizes the temperature, pH value, current density, gold concentration and indium concentration, so as to form a gold plating layer doped with indium on the surface of the workpiece. The doping of indium can increase the hardness of the gold plating layer, help reduce the wear of the gold plating layer, and improve the durability of the gold-plated workpiece.

[0027] 2. In the present application, nano silicon carbide and modified silicon carbide are preferably used as anti-wear agents, and the anti-wear agents are doped into the gold plating layer, which further increases the hardness of the gold plating layer and improves the durability of the gold-plated workpiece. DETAILED DESCRIPTION

[0028] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.

[0029] Preparation example of modified silicon carbide

[0030] The following is an explanation using a preparation example.

[0031] Preparation Example 1 In this preparation example, modified silicon carbide is prepared according to the following method:

[0032] (1) Use distilled water to wash the wear-resistant silicon carbide, then dry the nano silicon carbide at 110°C, mix the nano silicon carbide and toluene in a ratio of 1g:6mL, stir at a rate of 300rpm for 10min under nitrogen protection, then add a silane coupling agent, continue stirring and reacting at 90°C for 5h, filter while hot after the reaction is completed, soak it in acetone twice and then filter it, and obtain silanized silicon carbide after drying; the silane coupling agents used in this step are KH550 and vinyl triethoxysilane, and the amount of both is 10% of the weight of the nano silicon carbide; (2) Silylated silicon carbide and acrylamide are added to deionized water, stirred at a rate of 300 rpm for 10 min, an initiator is added under nitrogen protection, and the mixture is stirred at 30°C for 3 h, followed by filtration, washing and drying to obtain modified silicon carbide. In this step, the amount of acrylamide is 1.5% of the weight of the silanized silicon carbide, the silanized silicon carbide is mixed with water at a ratio of 1 g:6 mL, and the initiator is ammonium cerium nitrate, and the amount thereof is 0.05% of the weight of the silanized silicon carbide.

[0033] As shown in Table 1, the difference between Preparation Examples 1-5 is that the percentage of acrylamide used in the weight of silanized silicon carbide (abbreviated as acrylamide percentage in Table 1) is different.

[0034] Table 1 Proportion of acrylamide sample Acrylamide percentage / % Preparation Example 1 1.5 Preparation Example 2 2.1 Preparation Example 3 2.9 Preparation Example 4 3.2 Preparation Example 5 3.5 Example

[0035] Examples 1-5 The following description is given by taking Example 1 as an example.

[0036] Example 1 This embodiment provides a gold-indium electroplating process, comprising the following steps: (1) The workpiece is subjected to organic solvent degreasing, chemical degreasing, pickling and rust removal, pickling activation, pre-nickel plating, and citric acid immersion treatment in sequence, and then set aside; in this step, the material of the workpiece is red copper with a purity of 99.99%; (2) Platinum-coated titanium mesh was used as the anode material in a citrate plating solution with a pH value of 5 (referred to as pH in Table 2) and a temperature of 40°C (referred to as plating solution temperature in Table 2) at a rate of 0.2 A / dm 2The workpiece was gold-plated at a current density of 1.37 W (referred to as current density in Table 2) to form a 12 μm thick coating on the surface of the workpiece. After the treatment, the workpiece was recovered and washed with alcohol and dried to obtain a gold-plated workpiece. The components of the citrate gold plating solution include citric acid, main salt and citrate, the main salt is potassium gold cyanide, and the citrate is indium citrate, ammonium citrate, sodium citrate and potassium citrate, wherein the concentration of citric acid is 38 g / L, the concentration of ammonium citrate is 65 g / L, the concentration of sodium citrate and potassium citrate are both 20 g / L, and the gold concentration and indium concentration in the citrate gold plating solution are 4 g / L and 1 g / L, respectively.

[0037] In the above process, the specific operation process of step (1) is as follows: (1) The sample was ultrasonically cleaned in acetone for 5 min to complete the degreasing of organic solvents; (2) Wash the workpiece for 25 min in a chemical degreasing liquid with a concentration of sodium hydroxide, sodium phosphate, sodium carbonate, and OP emulsifier of 10 g / L, 45 g / L, 25 g / L, and 2 g / L at a temperature of 85°C to complete chemical degreasing; (3) Soak the workpiece in 4 mol / L dilute hydrochloric acid for 10 min to complete pickling and rust removal; (4) Immerse the workpiece in 35g / L sulfuric acid for 60s, then wash and complete the pickling activation; (5) Pre-nickel plating the workpiece using a commercially available aminosulfonate plating solution to form a nickel plating layer with a thickness of 2.3 mm (referred to as the nickel plating layer thickness in Table 2) on the surface of the workpiece, completing the pre-nickel plating treatment; (6) Immerse the workpiece in a 20wt% citric acid solution, then take the workpiece out to complete the citric acid immersion treatment.

[0038] As shown in Table 2, the differences between Examples 1-5 mainly lie in the different production and processing parameters of the electroplating process.

[0039] Table 2 Production and processing parameters of electroplating process sample Example 1 Example 2 Example 3 Example 4 Example 5 pH 5 4.8 4.5 4.3 4 Bath temperature / ℃ 40 45 50 55 60 <![CDATA[Current density / (A / dm 2 )]]> 0.2 0.5 0.8 1.1 1.5 Gold concentration / (g / L) 4 6 7 8 10 Indium concentration / (g / L) 1 3 5 7 10 Nickel plating thickness / mm 2.3 2.4 2.5 2.7 2.8 Example 6

[0040] The difference between this embodiment and embodiment 5 is that the main salt is composed of potassium gold cyanide and potassium gold citrate, and under the condition of a gold concentration of 10 g / L, the concentration of potassium gold citrate is 2 g / L.

[0041] As shown in Table 3, the difference between Examples 6-10 is that the concentration of potassium gold citrate is different.

[0042] Table 3 sample Concentration of gold potassium citrate / (g / L) Example 6 2 Example 7 2.2 Example 8 2.5 Example 9 2.8 Example 10 3 Examples 11-15 The difference between Example 11-15 and Example 6-10 is that Example 11-15 is obtained by adjusting the current density in sequence on the basis of Example 6-10. The specific settings of potassium gold citrate concentration and current density of Example 11-15 are shown in Table 4.

[0043] Table 4 Gold potassium citrate concentration and current density sample Concentration of gold potassium citrate / (g / L) <![CDATA[Current density / (A / dm 2 )]]> Embodiment 11 2 0.3 Example 12 2.2 0.4 Embodiment 13 2.5 0.5 Embodiment 14 2.8 0.7 Embodiment 15 3 0.9 Examples 16-20 The difference between Example 16-20 and Example 11-15 is that Example 16-20 is obtained by adding potassium antimony tartrate in turn to Example 11-15. The specific settings of potassium antimony tartrate concentration, potassium gold citrate concentration and current density of Example 16-20 are shown in Table 5.

[0044] Table 5 Antimony potassium tartrate concentration, gold potassium citrate concentration and current density sample Concentration of gold potassium citrate / (g / L) <![CDATA[Current density / (A / dm 2 )]]> Concentration of potassium antimony tartrate / (g / L) Example 16 2 0.3 0.08 Embodiment 17 2.2 0.4 0.13 Embodiment 18 2.5 0.5 0.17 Embodiment 19 2.8 0.7 0.22 Embodiment 20 3 0.9 0.26 Embodiment 21

[0045] The difference between this embodiment and embodiment 20 is that an anti-wear agent is added to the citrate gold plating solution before the workpiece is gold-plated. The anti-wear agent is nano-silicon carbide, and the addition amount of nano-silicon carbide is 2 g / L. The anti-wear agent is added in the following manner: the anti-wear agent and the citrate gold plating solution are mixed in a weight ratio of 2:1, and then the mixture is added to a plating tank filled with the citrate gold plating solution, and magnetic stirring is performed. During the stirring process, a dispersant is added to the plating tank, and ultrasonic dispersion treatment is performed after stirring for a period of time to complete the addition of the anti-wear agent.

[0046] As shown in Table 6, the difference between Examples 21-25 is that the amount of nano-silicon carbide used is different.

[0047] Table 6 Amount of Nano-SiC sample Amount of Nano-SiC / (g / L) Embodiment 21 2 Embodiment 22 4 Embodiment 23 5 Embodiment 24 6 Embodiment 25 8 Embodiment 26

[0048] The difference between this embodiment and Example 25 is that the anti-wear agent is nano silicon carbide and modified silicon carbide of Preparation Example 1, wherein the amount of nano silicon carbide is 2 g / L and the amount of modified silicon carbide is 1.5 g / L.

[0049] As shown in Table 7, the difference between Examples 26-30 is that the preparation examples of modified silicon carbide are different.

[0050] Table 7 Preparation example of modified silicon carbide sample Preparation Example Embodiment 26 Preparation Example 1 Embodiment 27 Preparation Example 2 Embodiment 28 Preparation Example 3 Embodiment 29 Preparation Example 4 Embodiment 30 Preparation Example 5 Examples 30-34 As shown in Table 8, the difference between Examples 30-34 is that the amount of modified silicon carbide added is different.

[0051] Table 8 Addition amount of modified silicon carbide sample Modified silicon carbide addition amount / (g / L) Embodiment 30 1.5 Embodiment 31 2.1 Embodiment 32 2.7 Embodiment 33 3.5 Embodiment 34 4.2 Comparative Example Comparative Example 1

[0052] A gold electroplating process comprises the following steps: (1) The workpiece is subjected to organic solvent degreasing, chemical degreasing, pickling and rust removal, pickling activation, pre-nickel plating, and citric acid immersion treatment in sequence, and then set aside; in this step, the material of the workpiece is red copper with a purity of 99.99%; (2) Platinum-coated titanium mesh was used as the anode material in a citrate plating solution with a pH of 5 and a temperature of 40°C at a rate of 0.2 A / dm 2 The workpiece is gold-plated at a current density of , forming a 12μm thick coating on the surface of the workpiece, and the workpiece is recovered after the treatment, and the gold-plated workpiece is obtained after alcohol washing and drying; the components of the citrate gold plating solution include citric acid, main salt and citrate, the main salt is potassium gold cyanide, the citrate is ammonium citrate, sodium citrate and potassium citrate, wherein the concentration of citric acid is 38g / L, the concentration of ammonium citrate is 65g / L, the concentration of sodium citrate and potassium citrate are both 20g / L, and the gold concentration in the citrate gold plating solution is 4g / L.

[0053] In the above process, the specific operation process of step (1) is as follows: (1) The sample was ultrasonically cleaned in acetone for 5 min to complete the degreasing of organic solvents; (2) Wash the workpiece for 25 min in a chemical degreasing liquid with a concentration of sodium hydroxide, sodium phosphate, sodium carbonate, and OP emulsifier of 10 g / L, 45 g / L, 25 g / L, and 2 g / L at a temperature of 85°C to complete chemical degreasing; (3) Soak the workpiece in 4 mol / L dilute hydrochloric acid for 10 min to complete pickling and rust removal; (4) Immerse the workpiece in 35g / L sulfuric acid for 60s, then wash and complete the pickling activation; (5) Pre-nickel plating the workpiece using a commercially available aminosulfonate plating solution to form a 2.3 mm thick nickel plating layer on the surface of the workpiece, completing the pre-nickel plating treatment; (6) Immerse the workpiece in a 20wt% citric acid solution, then take the workpiece out to complete the citric acid immersion treatment. Comparative Example 2

[0054] The difference between this comparative example and Example 1 is that the indium concentration in the citrate gold plating solution is 0.5 g / L. Performance testing methods

[0055] A copper sheet with a purity of 99.99%, a size of 10mm×20mm×3mm, polished to smoothness by 220#-800# water sandpaper step by step, and dehydrated and dried with anhydrous ethanol was used as a workpiece, and electroplated in accordance with the methods of the embodiments and comparative examples to form a coating on the surface of the copper sheet, and then the microhardness of the gold coating was measured using an MH-6 Vickers hardness tester, and the test conditions were 25g load and maintained for 10s. Each embodiment and comparative example was repeated 10 times and averaged, and the average value of 10 times was used as the final result, and then the microhardness of comparative example 1 was used as a benchmark to calculate the ratio between the microhardness measured in each embodiment and comparative example and the microhardness of comparative example 1, and the ratio was recorded as the relative hardness, and the results are shown in Table 9.

[0056] Table 9 Relative hardness sample Relative hardness / % sample Relative hardness / % Example 1 192.5 Embodiment 19 206.1 Example 2 203.7 Embodiment 20 207.5 Example 3 207.9 Embodiment 21 219.4 Example 4 211.4 Embodiment 22 221.7 Example 5 216.8 Embodiment 23 225.6 Example 6 217.0 Embodiment 24 228.9 Example 7 216.9 Embodiment 25 233.6 Example 8 217.2 Embodiment 26 224.5 Example 9 217.3 Embodiment 27 226.9 Example 10 217.5 Embodiment 28 228.1 Embodiment 11 190.8 Embodiment 29 233.5 Example 12 187.2 Embodiment 30 236.6 Embodiment 13 185.5 Embodiment 31 240.6 Embodiment 14 182.7 Embodiment 32 247.8 Embodiment 15 178.4 Embodiment 33 255.4 Example 16 202.7 Embodiment 34 263.5 Embodiment 17 204.5 Comparative Example 1 100.0 Embodiment 18 205.3 Comparative Example 2 143.2 Combining Examples 1-5 and Comparative Example 1 and Table 9, it can be seen that the microhardness measured in Examples 1-5 is significantly higher than that in Comparative Example 1, indicating that the gold plating obtained by the method of the present application has a higher hardness and therefore has better wear resistance, thereby enhancing the durability of the gold-plated workpiece and overcoming the defects in the related art.

[0057] Combining Example 3 and Comparative Example 2 with Table 9, it can be seen that when the indium concentration in the citrate gold plating solution is lower than the lower limit specified in the present application, the hardness of the gold plating layer will decrease significantly.

[0058] Combining Example 5 with Examples 6-10 and Table 9, it can be seen that at 1.5 A / dm 2 Under the current density condition, using potassium citrate as the second component of the main salt can still enable the gold plating layer to maintain good hardness performance.

[0059] It can be seen from Examples 6-10, Examples 11-15 and Table 9 that, when the current density is relatively low, the addition of potassium citrate gold has an adverse effect on improving the hardness of the gold coating.

[0060] Combining Examples 11-15, Examples 16-20 and Table 9, it can be seen that the microhardness measured in Examples 16-20 is higher than that in Examples 11-15, indicating that the addition of potassium antimony tartrate can overcome the microhardness of potassium gold citrate at 0.3-0.9 A / dm 2 The defect of poor deposition effect under current density conditions helps to obtain a gold plating layer with higher hardness.

[0061] It can be seen from Example 20, Examples 21-25 and Table 9 that the addition of the anti-wear agent nano-silicon carbide increases the hardness of the gold plating layer and improves the anti-wear performance of the gold plating layer.

[0062] It can be seen from Example 25, Examples 26-30 and Table 9 that compared with nano-silicon carbide, modified silicon carbide has a better effect on improving the hardness of the gold plating. This is because there are a large number of amino groups on the surface of the modified silicon carbide, which are protonated in the acidic environment of the citrate gold plating solution and carry a positive charge. Under the action of the electric field, it can more easily migrate to the surface of the workpiece and then deposit on the surface of the workpiece, which helps to fully improve the hardness performance of the gold plating.

[0063] It can be seen from Examples 30-34 and Table 9 that when the addition amount of modified silicon carbide is 2.7-4.2 g / L, the total amount of anti-wear agent can still be maintained at a relatively low level (compared with the maximum amount when only nano-silicon carbide is added), and the gold plating layer maintains good hardness performance.

[0064] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A gold-indium electroplating process, characterized in that: The following steps are involved: (1) sequentially subjecting the workpiece to organic solvent degreasing, chemical degreasing, pickling and rust removal, pickling and activation, pre-nickel plating, and citric acid immersion treatment, and setting aside; the pre-nickel plating treatment forms a 2.3-2.8 mm thick nickel plating layer on the surface of the workpiece; (2) In a citrate plating solution with a pH of 4-5 and a temperature of 40-60°C, the 2 The workpiece is subjected to gold plating treatment at a current density of , and the workpiece is recovered after the treatment, and the gold-plated workpiece is obtained after alcohol washing and drying; the components of the citrate gold plating solution include a main salt and a citrate, the main salt includes potassium gold cyanide, the citrate includes indium citrate, and the gold concentration and indium concentration of the citrate gold plating solution are 4-10g / L and 1-10g / L respectively.

2. The gold-indium electroplating process according to claim 1, characterized in that: The main salt also includes gold potassium citrate, and the concentration of the gold potassium citrate is 2-3 g / L.

3. The gold-indium electroplating process according to claim 2, characterized in that: In step (2) of the process, the current density is selected to be 0.3-0.9A / dm 2 , the components of the citrate electroplating solution also include potassium antimony tartrate.

4. The gold-indium electroplating process according to claim 3, characterized in that: The concentration of potassium antimony tartrate is 0.08-0.26 g / L.

5. The gold-indium electroplating process according to claim 3, characterized in that: In step (2), before the workpiece is subjected to gold plating, an anti-wear agent is added to the citrate gold plating solution, wherein the anti-wear agent comprises nano-silicon carbide, and the addition amount of the nano-silicon carbide is 2-8 g / L.

6. The gold-indium electroplating process according to claim 5, characterized in that: The anti-wear agent is added to the citrate gold plating solution according to the following method: The anti-wear agent is mixed with a portion of the citrate gold plating solution, and then the mixture is added into a plating tank containing the citrate gold plating solution and magnetically stirred. During the stirring process, a dispersant is added into the plating tank. After stirring for a period of time, ultrasonic dispersion treatment is performed to complete the addition of the anti-wear agent.

7. The gold-indium electroplating process according to claim 5, characterized in that: The added amount of the nano silicon carbide is 5-8 g / L.

8. The gold-indium electroplating process according to claim 5, characterized in that: The anti-wear agent also includes modified silicon carbide, and the modified silicon carbide is prepared according to the following method: (1) using distilled water to wash the wear-resistant silicon carbide, then drying the nano silicon carbide, mixing the nano silicon carbide and toluene, stirring for a period of time under nitrogen protection, then adding a silane coupling agent and continuing to stir and react for a period of time, filtering while hot after the reaction is completed, soaking in acetone and then filtering to obtain silanized silicon carbide; the silane coupling agent is KH550 and vinyl triethoxysilane; (2) adding silanized silicon carbide and acrylamide together into deionized water, adding an initiator under nitrogen protection, keeping warm and stirring for a period of time, filtering, washing and drying to obtain modified silicon carbide; The amount of acrylamide used is 1.5-3.5% of the weight of silanized silicon carbide.

9. The gold-indium electroplating process according to claim 8, characterized in that: The amount of acrylamide used is 2.9-3.5% of the weight of silanized silicon carbide.

10. The gold-indium electroplating process according to claim 9, characterized in that: The added amount of the modified silicon carbide is 2.7-4.2 g / L.